Design Allocation And Scheduling Hardware Compiler For Digital Data Processing In FPGA - Hiew, Fu San (2006)
In this project, a high-level language and its automated compiler are proposed to automatically transform the language into a synthesizable RTL-level VHDL design. The proposed language, named as Simple Algorithmic Language for Hardware Design (SALH), is simple to use and featured single-assignment, in which it can reduce the coding lengthiness.